Saint Jérôme, sentinelle d’une Église assiégée dans la Vida de San Jerónimo (1595) de fray José de Sigüenza - Pauline Renoux-Caron (Les Cahiers de Framespa)
As a doctor of the Church and as the translator of the Vulgate, Saint Jerome is a privileged figure of the Counter-Reformation. His qualities as a polemist and his taste for controversy allowed him to respond to modern heresies, in front of which he stood as the «sentinel» of the besieged Church. His position, which is in many ways similar to that of the Catholic Monarch Philip II, who was devoted to the defense of doctrinal purity, will be showed through the analysis of the Vida de San Jerónimo, which was published in 1595 by the hyeronimite friar José de Sigüenza. The latter attempted to clear the image of Saint Jerome, who had been caricatured a few decades earlier by Erasmus in the Vita Hieronymi (1516), but José de Sigüenza also used the figure of Saint Jerome to convey a more open approach to orthodoxy.